2016
DOI: 10.1016/j.biotechadv.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Structural traits and catalytic versatility of the lipases from the Candida rugosa-like family: A review

Abstract: Lipases and sterol esterases are enzymes with broad biotechnological applications, which catalyze the hydrolysis or synthesis of long-chain acylglycerols and sterol esters, respectively. In this paper, we review the current knowledge on the so-called Candida rugosa-like family of enzymes, whose members display in most cases affinity against the two substrates mentioned above. The family includes proteins with the α/β-hydrolase folding, sharing conserved motifs in their sequences, and common structural features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 100 publications
3
65
0
1
Order By: Relevance
“…In addition, the lipase activity is also related to the size and orientation of the channel. For example, the lipase from Aspergillus niger having a narrow and curved channel shows relatively low activity, while those from Ophiostoma piceae , Nectria haematococca and Trichoderma reesei have straightforward and wider channels and much higher activities (Barriuso et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lipase activity is also related to the size and orientation of the channel. For example, the lipase from Aspergillus niger having a narrow and curved channel shows relatively low activity, while those from Ophiostoma piceae , Nectria haematococca and Trichoderma reesei have straightforward and wider channels and much higher activities (Barriuso et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…True lipases display a hydrophobic lid structure on active-site that regulate the activity mechanism in the presence of interface oil-water, which rearranges its position leaving an open gate to the active center. Then, the position of the lid marks the difference between the open (active) or closed (inactive) forms of these proteins [21,22]. On the other hand, Fikers et al [23] and Lotti et al [24] reported the repression of lipase production caused by glucose from culture both.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, a criteria used to recognize these two kinds of catalysts, i.e., actuation by the nearness of an interface, additionally called "interfacial initiation," was discovered unacceptable for the arrangement of such proteins as a few lipases didn't show such marvel. Prominent cases of this phenomenon are Lip4 from Candida rugosa (Barriuso et al, 2016) and Candida antarctica B (Zisis et al, 2016). In addition, lipase and esterase accord themes portrayed by PROSITE database (Hulo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%